The Role and Importance of Competitive Intelligence with Particular Emphasis on Mystery Shopping - Vidov, Luana; Peša, Anita Radman; Bosna, Jurica (Oeconomica Jadertina, 2017)
Since organizations today are facing an intensive increase in global competition, dynamic business environment, and a rapid development of information and communication technologies, many world authors state that the main key for the survival, growth and development, are accurate, timely and relevant information. Therefore Competitive Intelligence – being a process through which an organization collects, analyzes and manages data and information from the competitive environment, is becoming more and more important, and that is why the authors of this paper are presenting its complete and actual overview. Mystery shopping (MS), as a form of CI, is considered to be one of the most powerful tools available to organizations that help managers and decision makers to identify areas that need improvement. The aim of the paper is to point out the importance and benefits that Competitive Intelligence and Mystery shopping are bringing to the companies that make use of them. Through the research of relevant scientific literature, the authors conclude that organizations are increasingly focusing on the development and improvement of CI and MS because it allows them to develop efficient and rapid responses to decisions made by the competition, achieve the desired goals, and improve their present and future position.
Keywords: Competitive Intelligence; Mystery Shopping; competitive environment; information